Biomimetic application of non-smooth surface characteristic in anti-sticking drill stem. (2018) - Yang, Xiaofeng; Xia, Re; Zhou, Hongwei; Guo, Lu; Zhang, Lijun
It is one of the common phenomenon that the drill stem could be easily stuck in soft stratum, which consequently affects the drilling efficiency seriously. A biomimetic method to relieve the sticking problem of the drill stem is presented and studied. The anti-sticky mechanism of the earthworm for its amazing burrowing in soft soil is investigated and probed further, figuring out the fact that the corrugated surface structure of earthworm could reduce the friction assistance and soil adhesion. Inspired by earthworm, biomimetic drill stem with corrugated surface is designed and applied in soft stratum drilling. The results show that the biomimetic drill stem could effectively avoid being stuck in soft stratum, and the torque and thrust of the biomimetic drill stem show a considerable decrease. The mechanism of its good anti-sticking ability is addressed, and the effects of wavelength on both torque and thrust are investigated for experimental and industrial optimisation.